ANALISIS PEMASARAN DAN STRATEGI PENGEMBANGAN KOMODITI KEDELAI DI DESA NIPA KALEMOAN KECAMATAN BUALEMO KABUPATEN BANGGAI - Enteding, Trianto (JSTT, 2016)
This research aims to identify the soybean commodity marketing, analyze the environmental strategies and determine the development strategy of soybean commodity development strategies at Nipa Kalemoan Village Bualemo Sub-district Banggai Regency. The data collection method is using simple random sampling and to determine alternative strategies using SWOT analysis. The results of this research showed that the income received by the respondent an average of Rp 9.233.844.41/1,81 ha/planting season, or an average of Rp 5.099.287,21/ha/planting season, there are two channels soybean marketing. The margin earned on a single channel of 1.625 / Kg and an efficient level of 1,79 %, while the margin earned two channels of 3.083 / Kg and efficient level of 2,78 %. Through of SWOT analysis method implementation in the forms of programming are implemented is 1). Doing outreach to farmers about the development of commodity soybeans by maximizing the use of land to expand the soybean farming. 2). Doing technical training or study visits to farmers' groups to the development of commodity soybean area is to improve the skills of farmers to increase production of commodity soybeans. 3). Promote the provision of access to market information in order to meet market demand. 4). Works toward improving the infrastructure to facilitate the farmers to do farming and distribution or marketing of soybean production. 5). To strive for capital to finance soybean farming. 6) Do counseling about the introduction of soy and soy cultivate a good way. 7). Doing coaching skills in processing soybeans into processed products or an increase in value of the commodity soybeans. 8). Conduct counseling on agribusiness opportunities for commodity soybeans.